Behavior dynamics of low-frequency MHD-fluctuations and main plasma parameters in U-3M torsatron in RF-heating mode - Pashnev, V.K.; Sorokovoy, E.L.; Petrushenya, A.A.; Ozherel’ev, F.I.; Baron, D.I. (Вопросы атомной науки и техники, 2016)
A significant decrease in the intensity of low-frequency MHD-activity is accompanied by sharp increase of plasma energy content in U-3M torsatron. Plasma is generated and heated by RF-fields with frequency of w = 0.8w(ci) and is in a mode of low frequency of collisions. A set of 15 magnetic sensors was installed in one of the poloidal cross-sections of torus. The poloidal component of magnetic field was registered. At some point of time there is a sharp decrease of MHD-activity of plasma with a simultaneous increase of plasma energy content.